Injectable Composite Hydrogel Stents for Bone Defect Management with Enhanced Osteogenesis and Angiogenesis - Chen Z; Jia M; Liu Y; Zhou H; Wang X; Wu M (International Journal of Nanomedicine)
Zhihong Chen,1– 3 Mingyu Jia,1,3 Yangyang Liu,1 Huajian Zhou,1,3 Xiaopan Wang,1 Min Wu1,3 1Department of Orthopedics, The First Affiliated Hospital of Bengbu Medical University, Bengbu Medical University, Bengbu, People’s Republic of China; 2Department of Orthopedics, Fenjinting Hospital in Sihong, Suqian, People’s Republic of China; 3Anhui Province Key Laboratory of Tissue Transplantation, Bengbu Medical University, Bengbu, People’s Republic of ChinaCorrespondence: Min Wu, Department of Orthopedics, The First Affiliated Hospital of Bengbu Medical University, Bengbu Medical University, Bengbu, Anhui, 233004, People’s Republic of China, Tel + 86 13865032636, Email wumin197010@163.com Xiaopan Wang, Department of Orthopedics, The First Affiliated Hospital of Bengbu Medical University, Bengbu Medical University, Bengbu, Anhui, 233004, People’s Republic of China, Tel + 86 18715235275, Email wxpan123@163.comBackground: The use of autologous bone grafting is considered the most successful method for managing bone defects, particularly when utilizing cancellous bone grafts for the best outcomes. Nonetheless, the scarcity of cancellous bone presents a notable obstacle in remedying these defects. Consequently, it is essential to create reliable alternatives to cancellous bone grafts to ensure effective management of bone defects.Methods: In this research, we created an injectable composite hydrogel stents using gelatin methacrylate (GelMA) hydrogel to mimic the collagen properties of cancellous bone, along with the inclusion of nanohydroxyapatite (nHA) to signify the inorganic element. Furthermore, we incorporated vascular endothelial growth factor (VEGF) to improve regenerative vascular capabilities. Before being implanted into rat cranium defect models, these composite hydrogel stents were co-cultured with human umbilical vein endothelial cells (HUVEC) and bone marrow mesenchymal stem cells (BMSC).Results: The composite hydrogel stents exhibited a network structure with porosity, robust mechanical properties, and beneficial degradation traits. In the degradation phase, it steadily releases Ca²⁺ and VEGF, which encourages the proliferation, migration, and osteogenic differentiation of BMSCs from rats. Moreover, this release improves the ability of HUVECs to form tubes. Collectively, these mechanisms support the regeneration of blood vessels and bone in the cranium defect region of rats.Conclusion: The composite hydrogel stents demonstrated excellent cytocompatibility and biological characteristics, as evidenced by its ability to enhance both osteogenesis and angiogenesis in vivo and in vitro. Consequently, it has the potential to act as an effective alternative to natural cancellous bone.Keywords: nano-hydroxyapatite, vascular endothelial growth factor, laser speckle blood flow imager, bone tissue engineering